(untitled) (World Bulletin of Management and Law, 2026)
This article examines the theoretical and practical need to integrate environmental responsibility into public policy and the law-making system within the framework of sustainable development. The study focuses on Strategic Environmental Assessment (SEA) as a preventive legal and policy instrument for forecasting the environmental consequences of draft laws, state programs, and strategic decisions before their adoption. Using comparative, systemic, and analytical methods, the article distinguishes SEA from environmental expertise and substantiates its importance as a strategic mechanism of environmental governance. The results show that SEA contributes to preventing ecological risks, improving policy quality, strengthening scientific justification in legislation, and aligning national lawmaking with sustainable development goals. The article also proposes institutional directions for Uzbekistan, including digital environmental governance, territorial differentiation of assessment, and proactive environmental filtering in industrial, energy, and infrastructure policy.